Workshop Technopreneurship Pembuatan Video Promosi Dengan Anggaran Yang Efisien Dan Mengedepankan Hak Cipta Pada Siswa SMK PGRI Sukoharjo - Ramadhian Agus Triono Sudalyo; Nurita Elfani Prasetyaningrum; Gesang Kristianto Nugrohotomo (CV. Multi Kreasi Media, 2023)
Promotional videos are videos used to build awareness of initiatives, product or service launches, marketing, sales, and programs. Basically, any video that promotes one or more brand elements is a promo video. Making a promotional video is like realizing a vision for the intended segmentation. This breakthrough is an effort to communicate to consumers and customers why business managers need a brand on the products and services launched. There are several reasons why any business that has just been started or a business that is running established needs to use promotional videos and are considered important for the continuity of the business being run, including: 1) to get more consumers to transact to buy products or services, consumers are interested in product launches / services, including product and service programs of a business; 2) to build more activity and engagement on social media management; 3) to gain credibility from consumers; 4) so ​​that the message is conveyed with a strong and riveting message; 5) promotion strategy for business brands with a low budget, high impact; and 6) through promotional videos, you can introduce products, services, events and programs on various social platforms, websites/blogs, including via email marketing, and so on. However, because of the importance of promotional videos, it turns out that many business actors do not understand it, only to find business idea initiatives, without a strategy to influence consumers through reliable promotional videos. Surakarta University through the Higher Education Tridarma which consists of Education, Research and Community Service according to its legal basis in Law Number. 12, article 1 paragraph 9 concerning higher education. These three are important points in realizing the vision of the university. Community Service activities were carried out at the PGRI Sukoharjo Vocational School with four implementing lecturers consisting of the Informatics Engineering Study Program and the Accounting Study Program, namely Ramadhian Agus Triono Sudalyo as Chair of Community Service, Nurita Elfani Prasetyaningrum and Gesang Kristianto Nugroho the two of them as member. As a result of the Community Service in the workshop for making promotional videos with an efficient budget and prioritizing copyright, the 16 participants experienced new experiences starting from getting to know the world of business, promotion, finance, and copyright as a preparation for becoming entrepreneurs.